Use of electroconvulsive therapy in an adolescent patient with catatonia - Sandeep Grover; Natasha Kate; Gaurav Gupta (Indian Journal of Psychological Medicine, 2014)
There is lot of skepticism about the use of electroconvulsive therapy (ECT) in children and adolescents. However, available literature suggests that use of ECT can be at times life-saving in adolescents, especially those presenting with severe catatonia. We treated a 16-year-old female who presented to us with catatonia with a course of nine ECTs, with which she showed marked improvement. Review of the literature suggests that ECT should be considered as the second line treatment in the management of catatonia in adolescents.